Community Health Insurance Schemes and Access to Quality Health Services in Rural Areas: A Case of Kasaana Sub-County, Sheema District, Uganda - Nuwagaba, Ronald; Moses, Agaba (American Journal of Humanities and Social Sciences Research, 2022)
The study assessed the effect of community health insurance schemes on access to quality health services in rural areas in Kasaana Sub-County, Sheema District, Uganda. It was guided by the following objectives; to find out the effect of health infrastructure insurance scheme on the accessibility to quality health services, to determine the extent to which medical materials insurance scheme influence the accessibility to quality health services and to find out the extent to which financial resource insurance scheme affect the accessibility to quality health services.The researcher used a correlation and cross sectional designs. The researcher used both purposive and stratified random sampling techniques to sample respondents and the sample size was 310 respondents. Pearson Correlation Coefficient was also used first to examine associations between variables, presented in a correlation matrix style. Finally, a sequence of Multiple Regression Analyses was employed to test the hypothesis and to identify the nature and extent of relationship. The study findings revealed that effectiveness of health infrastructure has a strong, positive and significant impact on people’s accessibility to quality health services (R-value of 0.983; Beta value of 0.983 and significant value of 0.00). The study findings also revealed that availability of medical facilities or material at health centers have a positive impact on the accessibility of quality health service to people (r-value of 0.979 and Beta value of 0.979 at significant value of 0.00). It was also revealed that availability of financial resources insurance schemes have a strong, positive and significant impact on people’s accessibility to quality health services (r-value of 0.998, Beta value of 0.998 and significant value of 0.00.) This study concluded that effective health infrastructure insurance has a strong, positive and significant impact on the people’s accessibility to quality health services. The government should ensure that laboratories at all heath facilities that are well equipped with facilities such that patients can access laboratory related services easily